2012
DOI: 10.2319/031212-217.1
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status of adult patients treated with fixed buccal appliances and removable aligners over one year of active orthodontic therapy

Abstract: These results suggest treatment with fixed buccal orthodontic appliances is associated with decreased periodontal status and increased levels of periodontopathic bacteria when compared to treatment with removable aligners over the 12-month study duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 32 publications
5
78
0
17
Order By: Relevance
“…Although a direct comparison is not possible, our results are similar to those of a previous study showing that lower numbers of anaerobic bacteria, less plaque accumulation, and improved periodontal conditions were found with removable aligners compared with fixed appliances. 24 The present study shows that removal of fixed appliances does not significantly reduce all periodontal pathogens during the initial retention period. Therefore, our null hypothesis was partly accepted.…”
Section: Discussionmentioning
confidence: 76%
“…Although a direct comparison is not possible, our results are similar to those of a previous study showing that lower numbers of anaerobic bacteria, less plaque accumulation, and improved periodontal conditions were found with removable aligners compared with fixed appliances. 24 The present study shows that removal of fixed appliances does not significantly reduce all periodontal pathogens during the initial retention period. Therefore, our null hypothesis was partly accepted.…”
Section: Discussionmentioning
confidence: 76%
“…Pada tahap akut, rawatan ortodontik boleh menyebabkan kesakitan dan keradangan gusi (Erdinç & Dinçer 2004;Long et al 2013;Tecco et al 2009), mengganggu pertuturan (Long et al 2013) dan menyebabkan penyakit periodontal (Karkhanechi et al 2013). Walau bagaimanapun, kajian terhadap kesan jangka masa panjang rawatan ortodontik menunjukkan tiada perbezaan yang ketara dalam kejadian karies, penyakit periodontal atau kehilangan gigi antara individu yang mendapatkan dan tidak mendapatkan rawatan ortodontik (Thomson 2002) .…”
Section: Pendahuluanunclassified
“…However, during its course gingival hypertrophy, accumulation of plaque and calculus formation can occur 14 , increasing the levels of periodontopathogenic lationship between orthodontic treatment and NUG. Lira et al have reported the therapeutic success of using 500mg of metronidazole and chlorhexidine 0.12% mouthwashes in a patient with NUG and under orthodontic treatment 4 .…”
Section: Discussionmentioning
confidence: 99%